2020
DOI: 10.7322/jhgd.v30.10381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inspiratory muscle training and breathing exercises in children with asthma: a systematic review

Abstract: Introduction: Asthma is characterized by a narrowing and inflammation of the bronchi, with symptoms of dyspnea, fatigue and exercise limitation. Physical therapy includes inspiratory muscle training and breathing exercises, given that an increase in inspiratory muscle strength and resistance can improve the symptoms of the disease. Objective: To describe the effects of inspiratory muscle training (IMT) and breathing exercises in children with asthma. Methods: This is a systematic review of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Similarly, IMT was reported to cause significant increases in respiratory muscle strength for 6 weeks [ 36 ] and 12 weeks [ 40 ]. A meta-analysis was carried out in favor of increasing PImax during IMT, but PEmax results were controversial [ 4 ]. There are three possible explanations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, IMT was reported to cause significant increases in respiratory muscle strength for 6 weeks [ 36 ] and 12 weeks [ 40 ]. A meta-analysis was carried out in favor of increasing PImax during IMT, but PEmax results were controversial [ 4 ]. There are three possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Breathing exercises (BTE) and inspiratory muscle training (IMT) are nonpharmacological interventions that improve asthma control. Both exercises have been widely used and are low cost, easy to apply, safe, and considered important adjuncts for asthma treatment [ 4 ]. BTE have been routinely used by professionals to control the hyperventilation symptoms of asthma and often appear in educational programs as self-monitoring techniques, which aim to adapt asthma patients to an appropriate breathing pattern with a longer expiration and a lower respiratory rate and thereby reduce hyperventilation and hyperinflation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of threshold IMT (15)(16)(17) and IS (18,19) training among obese adults reported substantial improvement in 6-min walk test (6-MWT) distance, inspiratory muscle strength, and spirometry. In children and adolescents, studies of the effect of threshold IMT (20)(21)(22)(23)(24)(25)(26)(27) and IS (28)(29)(30) on pulmonary function were conducted in other diseases, including neuromuscular disease (NMD), cerebral palsy (CP), asthma, and cystic fibrosis (CF). To our knowledge, no study has investigated the effect of threshold IMT and IS on functional fitness, RMS, and spirometry in children and adolescents with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Topics such as the effect of interdisciplinary intervention on insulin resistance indicators in overweight adolescents 25 and the use of surface electromyography as a measure of physical therapy outcome in children with cerebral palsy 26 are presented in this volume. This publication also contains the comparison of click and ce-chirp stimuli in hearing screening in the neonatal life cycle stage 27 and the effects of inspiratory muscle training and breathing exercises in children with asthma 28 , close the themes related to the life cycle of childhood and adolescence.…”
mentioning
confidence: 99%